Chemical reactions on adsorbing surface: kinetic level of description - Kostrobii, P.P.; Rudavskii, Yu.K.; Ignatyuk, V.V.; Tokarchuk, M.V. (Condensed Matter Physics, 2003)
Based on the effective Hubbard model we suggest a statistical description of reaction-diffusion processes for bimolecular chemical reactions of gas particles adsorbed on the metallic surface. The system of transport equations for description of particles diffusion as well as reactions is obtained. We carry out the analysis of the contributions of all physical processes to the formation of diffusion coefficients and chemical reactions constants. На основі ефективної моделі Хаббарда запропоновано статистичний опис реакційно-дифузійних процесів для бімолекулярних хімічних реакцій між частинками газу, адсорбованими на металічній по- верхні. Отримано систему рівнянь переносу, що описують як дифузію частинок, так і хімічні реакції між ними. Проаналізовано вклади усіх фізичних процесів в формування коефіцієнтів дифузії та констант реакцій.